Toughest people to love : how to understand, lead, and love the difficult people in your life - including yourself - DeGroat, Chuck (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2014)
Explores the basics of how people "tick," encouraging leaders to examine and take care of themselves so that they can better understand and care for others. Based on DeGroat's wealth of experience as a pastor, professor, and therapist, this book -- both wise and practical -- is one that countless leaders will go back to time and again for valuable insights and renewed vision. --Publisher's description.
A vision for those we lead, a vision for ourselves -- Understanding our story -- Personality disorders : loving those who drive you crazy -- Addictions : loving in the dark -- Loving the fool : when relationships turn ugly -- Growing through pain : the gift of the dark -- Living with wholeness : rest and resiliency in the leader's life -- Growing into leadership maturity : self-care and the art of shadow-boxing.
Includes bibliographical references.
Keywords: Conflict management -- Religious aspects -- Christianity; Interpersonal conflict -- Religious aspects -- Christianity; Interpersonal relations -- Religious aspects -- Christianity; Love -- Religious aspects -- Christianity